2008
DOI: 10.1159/000135696
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Folded Recombinant Der p 5, a Potential Diagnostic Marker Allergen for House Dust Mite Allergy

Abstract: Background: Der p 5 was reported as an important allergen in Dermatophagoides pteronyssinus, which is particularly recognized by patients suffering from asthma. The aim of this study was to produce, by recombinant DNA technology, a folded Der p 5 allergen for diagnostic, therapeutic and preventive purposes. Methods: Der p 5-encoding cDNA was isolated from a λgt11 D. pteronyssinus expression cDNA library and expressed in Escherichia coli. rDer p 5 was purified to homogeneity and characterized by mass spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…6) indicated that the Der p 21 allergen was dimeric (21). Studies of immuno-stained mites noted that Der p 5 appeared on fibrous structures in the food ball (10). In combination with the present results, these observations suggest that Der p 5 may be an integral structural component of these fibers given the apparent proclivity to polymerize.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…6) indicated that the Der p 21 allergen was dimeric (21). Studies of immuno-stained mites noted that Der p 5 appeared on fibrous structures in the food ball (10). In combination with the present results, these observations suggest that Der p 5 may be an integral structural component of these fibers given the apparent proclivity to polymerize.…”
Section: Discussionsupporting
confidence: 75%
“…The structure of Blo t 5 was determined in two studies using NMR (19,20). Both studies confirmed the results of CD spectroscopy and bioinformatics predictions of other group 5 and the highly similar group 21 mite allergens, which suggested that the proteins were largely helical in nature (10,(21)(22)(23). A superficial comparison of the two protein structures of Blo t 5 (2JMH and 2JRK in the Protein Data Bank) shows two elongated proteins, both with three ␣-helices all in a parallel orientation, and a disordered N terminus.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…The bacterial cells were grown overnight in LuriaBertani medium containing 100 mg/l ampicillin at 28°C, and expression of the recombinant protein was induced by adding isopropyl-β-thiogalactopyranoside to a final concentration of 0.5 mM. After cultivation for additional 3 h at 37°C, E. coli were harvested by centrifugation (15 min, 3000 rpm, 4°C; Sorvall RC5C) and lysed as described previously (26). The lysed bacterial cells were centrifuged at 18,000 rpm, 20 min, 4°C, and proteins of the soluble fraction containing Der p 23 were treated with 60% ammonium sulfate for 1.5 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…rDer p 5, rDer p 21 and rDer p 23 were purified as previously described [32][33][34]. Recombinant Der p 7 was purified by hydrophobic interaction chromatography and hydroxyapatite chromatography while the clone 16-derived protein was purified by anion and cation exchange chromatography.…”
Section: Mite Allergens-recombinantmentioning
confidence: 99%